Novel Lipophilic Hydroxamates Based on Spirocarbocyclic Hydantoin Scaffolds with Potent Antiviral and Trypanocidal Activity - Vasiliki Pardali; Erofili Giannakopoulou; George Mpekoulis; Vassilina Tsopela; Georgios Panos; Martin C. Taylor; John M. Kelly; Niki Vassilaki; Grigoris Zoidis (MDPI AG, 2023)
Flaviviridae infections, such as those caused by hepatitis C (HCV) and dengue viruses (DENVs), represent global health risks. Infected people are in danger of developing chronic liver failure or hemorrhagic fever, both of which can be fatal if not treated. The tropical parasites Trypanosoma brucei and Trypanosoma cruzi cause enormous socioeconomic burdens in Sub-Saharan Africa and Latin America. Anti-HCV chemotherapy has severe adverse effects and is expensive, whereas dengue has no clinically authorized treatment. Antiparasitic medicines are often toxic and difficult to administer, and treatment failures are widely reported. There is an urgent need for new chemotherapies. Based on our previous research, we have undertaken structural modification of lead compound V with the goal of producing derivatives with both antiviral and trypanocidal activity. The novel spirocarbocyclic-substituted hydantoin analogs were designed, synthesized, and tested for antiviral activity against three HCV genotypes (1b, 3a, 4a), DENV, yellow fever virus (YFV), and two trypanosome species (T. brucei, T. cruzi). The optimization was successful and led to compounds with significant antiviral and trypanocidal activity and exceptional selectivity. Several modifications were made to further investigate the structure-activity relationships (SARs) and confirm the critical role of lipophilicity and conformational degrees of freedom.